KRITISCHE DISKURSANALYSE ZUR MANIFESTATIONEN DES FLÃœCHTLINGES IN ZEIT ONLINE - STEFANY DANO, PEGGY (IDENTITAET, 2017)
Since November 2015 problem of refugees in Germany trigger dispute either in the level of society and parties in parliament. Therefore, discourse of refugees in mass media in Germanydifferent one to another. Zeit Online is mass media in Germany, which its news based on background investigation and opinion on socal phenomenon. (www.zeit.de). According to this background, research question posed is how the manifestation of refugee in Zeit Online. This research aimed to describe manifestation of refugee in news. This research is qualitative research, which analyse five news articles from Zeit Online from April 2016 until August 2016. Theory Critical Discourse Analysys from Jäger is used in this research.  It analyze the relation between subject and object on  discourse which its meaning is manifested on linguistic features ( Jäger, 2001: 16).  This theory use synchronic and diachronic analysis. (Jäger, 2009: 200-202). Research results postulate that refugee is manifested as incompetence (unerwerbsfähig), uneducated (ungebilderte), poor (arm), high-cost maintenence (hochkostenwartung),and optimistic (optimistisch). These manifestations materialiszed through strategy and form of argumen, such as relativization, generalization, implicature, collective symbole and metaphore, and the use of spesific vocabulary. Discourse effect occured  affect reinforcement of refugee as others, who closely related to inferiority. Keywords: critical discourse analysis, manifestation, refugees.